The Impact of Significant Events on Public Policy and Institutional Change: Towards a Research Agenda - Patkauskaitė-Tiuchtienė, Inga; Bortkevičiūtė, Rasa; Nakrošis, Vitalis; Vilpišauskas, Ramūnas (Politologija, 2022)
Data shows that significant events such natural disasters, anthropogenic disasters and malign activities by hostile actors, often having cross-border effects, have been on the rise. However, the studies of the effects of those events on public policies, governance and institutions remain inconclusive. In this article we present a research agenda which proposes the classification of the significant events on the basis of their characteristics backing it with a newly compiled data set on significant events which took place in Lithuania in 2004-2020 and outline the directions for an in-depth analysis of the causal mechanisms of how those events affect policy and institutional change. We conclude with concrete proposals for further research which could provide theoretically innovative and policy relevant insights into the political processes which translate responses to significant events into policy and institutional changes affecting welfare institutions and resilience of society.